Filsafat Ilmu, Perkembangannya dan Pandangan Filsafat - Tarigan, Mardinal; Hamidiyah, Masita; Nasution, Masriyanti; Tanjung, Rahmi Rahmita (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Historically, philosophy has always been the mother of science. In its development, science is increasingly independent and concrete. However, in the face of many life problems that science cannot answer, philosophy became the basis for answering the problem. Before the 17th century, science was synonymous with philosophy. Philosophy itself is a broad science, meaningz that it is closelyz relatedz to our daily lives. Therefore, the philosophyz of sciencez can be seen as an attemptz to bridgez thez gapz betweenz philosophyz andz science. The urgency of the philosophyzof sciencez can be seen from its role asz a keyz dialogue partner in the development of science. The philosophy of science is also a philosophicalz reflectionz of the naturez ofz science, and does notz recognizez the end of the achievement of goals. Understandingz thez philosophyz ofz sciencez meansz understandingz thez complexity ofzscience, so thatz its mostz basicz aspectsz are also understood from the perspectivezofzscience, the development of science, and thez interrelationshipszbetween brancheszofzscience, which cannot be separated from a philosophical paradigm. Thez researchzmethod thatz researchersz usez when writingz scientificz papersz isz az typez of literature research. Itz can bezconcludedzthat philosophy is a sciencez thatz studiesz thez naturez of allz things. Sciencezis an objective way of thinkingzabout the real world and giving it meaning.